The Relationship between Nutritional Status and Fitness Test Performance of Atma Jaya University Marching Band Team - Wityadarda, Carissa; Andani, Gusti Ayu Sinta Deasy; Pareira, Elisabeth Matrona Sintia; Parulian, Adi Anggoro; Qomar, Nurul; Utomo, Datu Agung; Kion, Rivaldo; Situmorang, Novia Sari Fransisca; Purba, Erinaka Putri Sari; Nada, Patricia Angelica Variya; Fafiani, Salma (Journal of Community Empowerment for Health, 2025)
ABSTRACT Nutritional Status is one of the predictors of human energy balance. Adequate dietary intake plays an important role in providing human body with proper needs of nutrients such as carbohydrates, protein and fats which are converted into energy. The body's ability to produce adequate energy may be tied to the level of fitness it maintains, particularly in support of bodily functions, physical activity, and overall well-being. To find the correlation between dietary intake and fitness level, The team of coaches, doctor, nutritionist, physiotherapist, and medical record professional try to find the connection between nutrition intake of young adults of Marching band team’s and their physical fitness using Copper Fitness test. This study includes all 41 young adults of Marching Band’s team. The interview of nutrition intake was taken using an online food frequency questionnaire, meanwhile the Copper fitness test was taken directly under supervision of their fitness coaches at Yogyakarta. The result of Spearman Rank Correlation test between Body Mass Index (BMI) with Cooper fitness test result has negative correlation (r= -0.265, p=0.047), total dietary protein intake has positive correlation and statistically significant with Cooper fitness test result (r =0.287 and p= 0.034). On the other hand, other dietary intake such as total energy consumption, carbohydrates, fats and hydration have positive correlation with Copper Fitness test result (r=0.238, p=0.067, r=0.038, p=0.406; r= 0.065, p=0.344; r= 0.062, p=0.350). Considering these findings, it is essential for the marching band team to maintain their BMI and their dietary intake especially protein to maintain their muscle health to have an excellent fitness condition of their fitness level. However, the correlation might relatively weak means, it has another factor may also contribute to individual’s performance on the Cooper fitness test.